STUDENTS’ CREATIVITY IN WRITING SHORT STORIES VIEWED FROM SHORT STORY WRITING TECHNIQUES - Rayhan Nur Azizah; Dina Ramadhanti; Rahayu Fitri (Department of Master of Linguistic, Universitas Airlangga, 2026)
This study aims to describe the short story writing creativity of Grade XI Phase F students at SMAN 1 Salimpaung based on established short story writing techniques. The analysis focuses on six key aspects: opening the story, character development, plot construction, setting development, point of view, and story closure (Adapted from (Kosasih, 2008); (Aminudin., 2009); (Afrinda & Ramadhanti, 2018); (Ramadhanti & Yanda, 2022)). A qualitative descriptive method was employed, utilizing content analysis to examine data in the form of sentences and paragraphs extracted from students' written short stories. Data were collected through documentation analysis. The study was conducted during the first semester of the 2024/2025 academic year, involving students of Grade XI Phase F as research subjects. The findings reveal that the majority of students demonstrated a satisfactory level of creativity in applying short story writing techniques. Students were able to craft engaging story openings, develop characters through dynamic and vivid dramatization, and construct coherent plots from exposition to conflict resolution. Settings were described in rich sensory detail and aligned with the emotional states of the characters. The point of view was generally consistent and predominantly employed a third-person observer perspective. Story closures were notably effective in delivering emotional impact and leaving a lasting impression on the readers.